Quantifiers and Working Memory - Szymanik, Jakub; Zajenkowski, Marcin (Proceedings of the Amsterdam Colloquium, 2009)
The paper presents a study examining the role of working memory in quantifier verification. We created situations similar to the span task to compare numerical quantifiers of low and high rank, parity quantifiers and proportional quantifiers. The results enrich and support the data obtained previously in [1–3] and predictions drawn from a com putational model [4,5].